ETIKA KOMUNIKASI APARATUR PEMERINTAHAN KEPADA MASYARAKAT DI DESA CIBADUNG KECAMATAN GUNUNG SINDUR KABUPATEN BOGOR - Annie Rufeidah; Rahmayanti Rahmayanti; Unik Desthiani (Jurnal Pengabdian Sosial, 2023)
ABSTRACT   In general, in association or daily activities, ethics and communication are things that must be considered, this is because both are the basis for a person's behavior with other people in his environment. The definition of ethics itself is a behavior as a standard that regulates association in social groups, while communication is the process of conveying information both orally and in writing or pictures between two or more people to achieve a common goal. Communication ethics can be said as a principle that regulates relationships in interacting between humans, including norms, values or measures of behavior in communication activities in a society. Ethics of communication is needed in every human activity that has the goal of being able to convey information quickly, precisely and accurately as well as being able to build good relationships, as a form of courtesy in behaving, and being part of mutual respect or respect for others. Communication ethics has an important role in everyday life where the message conveyed will be easily received by others and can generate positive feedback. Communication ethics also plays a role in public services so that information can be conveyed and received properly to all levels of society. This explanation encouraged Pamulang University lecturers to hold community service activities (PKM) with the title "Ethics of Communication of Government Apparatuses to the Community in Cibadung Village, Gunungsindur District, Bogor Regency". The purpose of this PKM is to provide an understanding of the roles, benefits, and objectives of communication ethics for the smoothness and success of government apparatus in conveying information to the public. Keywords: ethics, communication, government apparatus